Zeebrugge ou l'émergence d'une nouvelle porte océane au cœur du Northern Range - Jacques Charlier; Valérie Lavaud-Letilleul (Territoire en Mouvement)
The latest developed among the Benelux seaports, Zeebrugge is considered in this paper as a functional complement to Antwerp within a regional port cluster, that is itself part of a world-class macrocluster including Amsterdam, Rotterdam, Antwerp and Zeebrugge at the heart of the most powerful european seaport range. Three new conceptual avenues are explored through Zeebrugge’s case study : co-opetition, clusterisation and terminalisation. They provide a framework to understand how, by also relying on a favourable geographical situation, a new oceanic gateway has recently emerged in the shadow of Antwerp and Rotterdam, based upon an unconventional trilogy : natural gas, containers and roro traffic.